As percepções dos moradores do Grotão da favela de Paraisópolis/SP sobre o processo de urbanização: as condições de vida e o direito à moradia - Werneck, Raquel Machado (2018)
The study presents the analysis of the perceptions of residents of the area of Grotão da Favela de Paraisópolis, located in the city of São Paulo / SP, related to the conditions of access to the right to housing and to the city, after the intervention of the Urbanization Program, considering its way of life and relations established in the territory. It emphasizes the feeling of belonging (or not), as well as the links and the identity with the territory, understanding this with living meaning and result of the action of the subjects that live in it. The study starts with the reflection about the process of formation of Brazilian cities and their conformations with patriarchal and hierarchical relations, in which the relations of power and interest of the dominant elites in the context of neoliberalism are preserved. Also, the understanding of the Housing Policy in the socio-historical process of social policies in Brazilian society. Despite the advances and achievements of the social movements, it is tried to reflect in what conditions the urbanization process of Paraisópolis provided a space of participation to the residents as protagonists protagonists, who analyze the Housing Policy as a historically vertical structure and with little popular participation. The centrality of the political subject as narrator is considered, for history must be told by those who live it. For this analysis, the qualitative methodology was used, which allows to reflect on the meanings, the interpretations and the protagonism of the subjects in their life histories related to the dwelling. Bibliographical and documentary researches were also used. The results indicate, from the interviewees' statements, a great discrepancy between what was proposed by the Favela Urbanization Program of Paraisópolis and the daily life of the residents, who show improvement in living conditions, but recognize the suffered urbanization process. They highlight the impact of the program on their lives, especially regarding the breaking of ties and relationships established in the territory. It is concluded that the relationship between the inhabitants' reality and the right to the city, in the search of the subjects in establishing their space in the society, is contradictory